Undoing work, preserving abstraction? A critique of the post-capitalism narrative of the “end of work” - Ayala-Colqui, Jesús; Barria-Asenjo, Nicol A.; Castillo Villapudua, Karla (Las Torres de Lucca. International Journal of Political Philosophy, 2026)
The aim of this article is the critique, from a conception fo capital as abstract domination, of the theoretical proposals of post-captialism of, on the one hand, Paul Mason and, on the other hand, Alex Williams, Nick Srnicek and Helen Hester. In these authors there is the idea of buiding a post-capitalist horizon where human beings stop working and break with mercantile logic through the use of information technologies. However, is it enough to stop working in order to exit capitalism? After presenting the main ideas of these authors, the text argues that their emphasis on the abolition of work does not address the dundamental split between concrete and abstract labor. Finally, some future research directions are briefly suggested, focused on how to think about emancipation without falling back into the abstraction of labor or the logic of the commodity.